Агрометеорологические условия и эффективность удобрений: учеб. пособие / Д. М. Хомяков - Хомяков Дмитрий Михайлович (Биология, 1990)
Экземпляры: КХ (20060329) / Инвентарный номер: 0287420 / Сис.шифр: 40.2 / Авт.знак: Х 76 / ГРНТИ: 68 / ББК: 40.2